Memory, Affectivity and Intimacy in Doris Lessing's Love, Again and Rosa Montero's La carne - Carmen García Navarro (Universitat de Barcelona, 2021)
This article discusses the literary approaches used by Doris Lessing in Love, Again (1995), and Rosa Montero in her novel La Carne (2016), emphasising the parallels between these writers' interest in women’s ageing experiences and the role that both of these novels’ main characters play in the contemporary cultural scene. Of particular interest in this article is the experience of these female authors who write these novels between the 1990s and the two first decades of the 21st century, historical periods which were marked by major social and economic upheaval, I suggest that their respective productions problematise the notions of memory, affectivity and intimacy, and notably showcase the contributions made by women in the process of ageing as creative agents of social and cultural changes in contemporary Europe.